(untitled) (Inovasi: Jurnal Diklat Keagamaan, 2016)
Basically learning is students’ rights. However, there are still a lot of students who do not learn in the classroom. Since a lot of students that do not learn, therefore the result of the learning is not maximum in other words the learning is not effective. That’s why one teachers forum is needed to improve the learning to be more effective which is called as lesson study . Concerning with that background above therefore this research aim is: a ) to know the level of achievement of lesson study at MTsN Prigen b ) to know the effectiveness of lesson study in improving the learning practice at MTsN Prigen. This research is qualitative descriptive study. The data collected by observation and interview was analyzed by using percentage and score. From the result and data analysis it is concluded that: a ) lesson study at MTs Prigen was ‘ good enough ‘implemented b ) the implementation of t lesson study at MTsN Prigen can improve the effectiveness of learning practice.